An Economical Internet of Things (IoT) Driven Approach for Non-Intrusive Smart Energy Monitoring - Fitri Wibowo; Suheri Suheri; Pausta Yugianus (G-Tech: Jurnal Teknologi Terapan, 2024)
This study focuses on the use of the Internet of Things (IoT) for non-intrusive monitoring of electricity consumption. Using Internet of Things technology, this study attempts to develop and evaluate an affordable and easy-to-navigate energy monitoring system. Literature review, system design, hardware development, software configuration, system integration, and system testing are all included in the methodology. The results demonstrate the successful use of an IoT device to track electrical energy consumption. The system demonstrates promising levels of accuracy in tracking power consumption patterns, despite ongoing testing and calibration challenges. This study provides an affordable and secure IoT-based smart energy monitoring solution.